2009
DOI: 10.1007/s10548-009-0123-4
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Combined TMS and EEG

Abstract: The combination of transcranial magnetic stimulation (TMS) with simultaneous electroencephalography (EEG) provides us the possibility to non-invasively probe the brain's excitability, time-resolved connectivity and instantaneous state. Early attempts to combine TMS and EEG suffered from the huge electromagnetic artifacts seen in EEG as a result of the electric field induced by the stimulus pulses. To deal with this problem, TMS-compatible EEG systems have been developed. However, even with amplifiers that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
355
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(368 citation statements)
references
References 130 publications
(218 reference statements)
6
355
1
6
Order By: Relevance
“…Finally, the time-course of LMFP effects over the motor cortex highlight that the tDCS modulates, in a polarity-specific manner, not only the initial component of cortical response, that is the correlate of the direct activation of the stimulated area, but also the later components, that is the markers of the activity triggered by axonally conducted signals (Ilmoniemi and Kicic, 2010). The hypothesized mechanism underlying that time-course could be represented by a differential balance between the intracortical (presumably GABAergic) inhibition or an enhancement of the intracortical (presumably glutamatergic) excitation, or by a mix of both.…”
Section: Tdcs-induced Changes In Cortical Excitabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…Finally, the time-course of LMFP effects over the motor cortex highlight that the tDCS modulates, in a polarity-specific manner, not only the initial component of cortical response, that is the correlate of the direct activation of the stimulated area, but also the later components, that is the markers of the activity triggered by axonally conducted signals (Ilmoniemi and Kicic, 2010). The hypothesized mechanism underlying that time-course could be represented by a differential balance between the intracortical (presumably GABAergic) inhibition or an enhancement of the intracortical (presumably glutamatergic) excitation, or by a mix of both.…”
Section: Tdcs-induced Changes In Cortical Excitabilitymentioning
confidence: 98%
“…The TMS-induced artifact was not removed from the recording (see Veniero et al, 2009). It is important to note that if an EEG epoch was rejected, the corresponding EMG epoch was also rejected (Ilmoniemi and Kicic, 2010), resulting in a one-to-one correspondence between cortical and peripheral measures.…”
Section: Tep Eeg and Mep Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…TMS-EEG facilitates a direct assessment of the cortical response to stimulation, removing the confounding influence of variations in spinal cord excitability that are known to effect conventional MEP measurements. In addition, combining these two methods provides significantly more information about the local and global response to ppTMS than can be derived from the MEP [21,22]. For LICI, previous studies utilising TMS-EEG in M1 have identified cortical indices of inhibition within TMS-evoked EEG potentials (TEPs), with specific TEP peaks produced by the test stimulus being reduced in amplitude when a conditioning stimulus is applied 100 ms earlier [23].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown promising results in the integration of transcranial magnetic stimulation (TMS) with simultaneous EEG for assessment of brain connectivity and cortical interactions. 11,12 treatMent of coMatose patients…”
Section: Electroencephalogram (Eeg)mentioning
confidence: 99%